Tracing Identity Traces: A Study of Chinese Crossbreed Literature in the Context of Indonesian Culture - Puspitasari, Edith Wenny; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Indonesia Sosial Sains, 2024)
This research article aims to explore the ways in which the Chinese Crossbreed community in Indonesia adapts and maintains its cultural identity in the midst of globalization. By exploring the experiences and perspectives of the younger generation, we hope to gain insight into the challenges and opportunities they face in preserving their heritage through literature. The research utilizes a qualitative approach, incorporating interviews, literary analysis, and ethnographic methods to capture a comprehensive view of the community's cultural dynamics.  Through this article, the author seeks to explain the importance of the contribution of the Chinese community to Indonesia's rich cultural landscape and the importance of fostering intercultural understanding and unity within the nation. The findings aim to provide a nuanced understanding of how globalization influences cultural preservation and the strategies employed by the Chinese Crossbreed community to navigate their dual heritage in contemporary Indonesian society.